2011
DOI: 10.1016/j.anorl.2010.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Titanium ossicular chain replacement prostheses: Prognostic factors and preliminary functional results

Abstract: Increasing the length of the ossicular prosthesis, especially TORP, may improve postoperative functional results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
46
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 20 publications
7
46
1
Order By: Relevance
“…Based on the MERI, Demir et al (10) have shown that the success rate is highly correlated with the pathophysiologic status of the middle ear independently from the type of replacement material. Indeed, different types of prosthesis for ossiculoplasty were compared, and no obvious differences were found by most studies (11)(12)(13)(14). Based on the OOPS, De Vos et al (15) found that the availability of the malleus handle, the status of the middle ear mucosa, and the status of the stapes footplate are significant predictors for hearing results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the MERI, Demir et al (10) have shown that the success rate is highly correlated with the pathophysiologic status of the middle ear independently from the type of replacement material. Indeed, different types of prosthesis for ossiculoplasty were compared, and no obvious differences were found by most studies (11)(12)(13)(14). Based on the OOPS, De Vos et al (15) found that the availability of the malleus handle, the status of the middle ear mucosa, and the status of the stapes footplate are significant predictors for hearing results.…”
Section: Discussionmentioning
confidence: 99%
“…The prostheses used in this study were Kürz titanium prostheses because of their biocompatibility and wellknown efficiency (11)(12)(13)(14). These prostheses have an open work head plate, which allows for good viewing when the TORP or PORP is placed.…”
Section: Discussionmentioning
confidence: 99%
“…Titanium implants are also MRI compatible. The cost of implant, however, becomes an important issue in the developing nations, especially when the cost of the second [1][2][3][12][13][14][15][16][17][18][19] The current study reports mean postoperative ABG of 13.8 ± 4 dB and closure of ABG to 20 dB or less in 95% of the patients.…”
Section: Discussionmentioning
confidence: 92%
“…Titanium is favored because of its rigidity, light weight, low impedance, and biocompatibilityand due to the open design of the prosthesis, which allow good viewing when the TORP or PORP is placed. [10][11][12][13][14][15] Coffey et al report that titanium ossicular prostheses provide superior hearing outcomes when compared to nontitanium prostheses. 10 In our study, we have only used the Kruz titanium prosthesis.…”
Section: Discussionmentioning
confidence: 99%